Fecal Calprotectin Is Highly Effective to Detect Endoscopic Ulcerations in Crohn's Disease Regardless of Disease Location. Issue 7 (27th October 2020) - Buisson, Anthony; Mak, Wing Yan; Andersen, Michael J; Lei, Donald; Pekow, Joel; Cohen, Russell D; Kahn, Stacy A; Pereira, Bruno; Rubin, David T
Abstract: Background: As the reliability of fecal calprotectin (Fcal) remains debatable to detect endoscopic ulcerations in patients with pure ileal Crohn's disease (CD), we aimed to compare its performances with those observed in patients with colonic or ileocolonic location. Methods: Using a prospectively maintained database, we analyzed 123 CD patients with Fcal measurement and ileocolonoscopy performed within 1 month with no therapeutic intervention during this interval. Receiver operating characterstic curves (ROC) were used to determine the best Fcal threshold to detect endoscopic ulcerations, taking into account the clinical relevance and usual recommended indices. Sensitivity, specificity, and positive (PPV) and negative predictive values (NPV) were presented with 95% confidence intervals. Results: The mean Fcal level was significantly higher in patients with endoscopic ulcerations in the L1 group ( P = 0.025) and the L2-L3 group ( P < 0.001). Using ROC curves, Fcal >200 µg/g and Fcal >250 µg/g were the best thresholds to detect endoscopic ulcerations in the L1 group (sensitivity = 75.0, 95% CI, 47.6–92.7; specificity = 87.5, 95% CI, 67.6–97.3; PPV = 80.0, 95% CI, 51.9–95.7; and NPV = 84.0; 95% CI, 63.9–95.5) and in the L2-L3 group (sensitivity = 84.1 95% CI, 69.9–93.4; specificity = 74.4, 95% CI, 57.9–87.0; PPV = 78.7, 95% CI, 64.3–89.3, and NPV = 80.6, 95% CI, 64.0–91.8), respectively. We compared the AUC between L1 and L2-L3 groups, and no difference was shown (0.89 vs 0.84, respectively, P = 0.46). We also compared 2-by-2 sensitivity, specificity, PPV, NPV, and accuracy and we did not observe any significant difference. Conclusion: Fecal calprotectin is highly effective to detect endoscopic ulcerations regardless of CD location but requires a lower cutoff value in patients with pure ileal involvement.